A Note on Singularly Perturbed System - Hengki Tasman; Theo Tuwankotta; Wono Setya Budhi (Institut Teknologi Bandung, 2002)
In this paper the solution of a singularly perturbed nonlinear ordinary differential equation which is obtained by using the asymptotic expansion method and a numerical method is analyzed in various values of the parameter of the equation. The numerical method which we use is Runge-Kutta-Feldbergh method of order 45, combined with the shooting method. Both solutions are verified using the first integral of the equation.